Model Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Sumber Daya di Madrasah Ibtidaiyah Ma’arif Giriliyo I Wukirsari Imogiri Bantul - Asmiyati Asmiyati (Jurnal Pendidikan Madrasah, 2018)
Madrasah education quality improvement is very related to the capacity and ability of the head master, because in the era of autonomy of education as currently the madrasa was given the freedom to develop the quality of education that exists in the madrasa. A model of leadership and how to lead the head of his Agency's response to the madrasa became one of the benchmark and the means to improve the quality of education in madrasah that she leads. The issues examined in this paper is focused on the model of leadership in improving the quality of head master resource madrasa MI Ma'arif Giriloyo I. This research is a descriptive research using qualitative approach, data collection is carried out by means of interviews, observation and documentation of data sources against primary and secondary. The results of this research show that; Value-based leadership is a leadership model in Madrasah Ibtidaiyah Giriloyo I basically a leadership that basing on the principle of cooperation from the head master resource components to the entire madrasa with values are developed within an organization as well as in line with religious values, social and Islamic culture around the madrasa. In the exercise of his leadership of the head master using principles of management i.e. input, process and output.